Measuring Citizens’ Perceptions of Access to Justice: A Quantitative Survey-Based Study on Legal Awareness, Affordability, and Trust in Judicial Institutions in Pakistan - Kokab Saeed; Nadia Noreen; Muhammad Rizwan; Sehrish Furyal; Irshan Arif; Anwar Ali (Al-Qanṭara, 2025)
This study examines citizens’ perceptions of access to justice in Pakistan by analysing legal awareness, affordability, judicial efficiency, institutional trust, and perceived barriers across three districts of the Hazara Division. Using a quantitative, survey-based design, data were collected from 200 respondents representing diverse socio-economic and demographic backgrounds. Findings show that while basic legal awareness is moderately high, significant gaps persist regarding procedural knowledge and availability of legal aid. Affordability emerged as a major obstacle, with many respondents viewing legal services and court-related expenses as financially burdensome. Perceptions of judicial efficiency were mixed, particularly concerning delays and lack of procedural clarity. Trust in judicial institutions was cautiously moderate, influenced positively by legal awareness and fairness perceptions but negatively affected by concerns over corruption and lack of independence. Regression analysis demonstrated that legal awareness, affordability, and judicial efficiency significantly predict institutional trust, whereas perceived barriers reduce it. A t-test revealed that women hold significantly higher trust compared to men, while a proportion test showed higher-than-expected citizen interaction with the justice system. Overall, the study highlights the urgent need for legal literacy programs, affordable legal aid, and system-wide reforms to strengthen access to justice in Pakistan.